Common fixed point theorems for cyclic contractive mappings in partial cone b-metric spaces and applications to integral equations - Zhu, Chuanxi; Xu, Wenqing; Došenovič, Tatjana; Golubovic, Zorana (Nonlinear Analysis: Modelling and Control, 2016)
In this paper, we introduce the concept of partial cone b-metric spaces as a generalization of partial metric, cone metric and b-metric spaces and establish some topological properties of partial cone b-metric spaces. Moreover, we also prove some common fixed point theorems for cyclic contractive mappings in such spaces. Our results generalize and extend the main results of Huang and Zhang [Cone metric spaces and fixed point theorems of contractive mappings, J. Math. Anal. Appl., 332:1468–1476, 2007], Stanić et al. [Common fixed point under contractive condition of Ćirić’s type on cone metric type spaces, Fixed Point Theory Appl., 2012:35, 2012] and Latif et al. [Fixed point results for generalized (α,ψ)‐Meir–Keeler contractive mappings and applications, J. Inequal. Appl., 2014:68, 2014]. Some examples and an application are given to support the usability of the obtained results.